Pengaruh Budaya Sekolah dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam di Sekolah SDN 06 Lalan - Milandari, Olvy; Setiawan, Farid; Nurhanifan, M. luthfi (ALSYS, 2022)
The success of implementing learning in schools cannot be separated from the influence from within each student. The success of a learner in learning is strongly influenced by various aspects of himself, one of which is his motivation in learning. Motivation in learning is not only obtained from family support, but also from how habits are formed in the school environment. The purpose of writing this article is to illustrate how influential the habits that grow in the school environment are for increasing a student's learning motivation, which will also affect the success of implementing learning in an educational institution. This research uses qualitative research methods using library study techniques, where we take various literature such as journals, articles, or books related to the influence of habits that grow in schools to increase learning motivation and also the authors collect data by interviewing public elementary school teachers. 06 LALAN to further strengthen the research that will be carried out. After taking some data both from the literature and interviews, the writer analyzes the data obtained and develops it into a piece of writing.